Parametric Exploration of Natural Lighting and Visual Comfort in Contemporary Additions to Historic Buildings - Şenalp, Mihrimah; Köymen, Erdem; Yaşa, Enes; Başar, Mehmet Emin; Köymen, Erdem (Solarlits, 2025)
The re-functioning of historical buildings frequently necessitates new additions. This is particularly relevant for historical buildings with open courtyards, where interventions often involve the installation of upper covers using contemporary materials and techniques This issue can become especially apparent in historical buildings that are completely enclosed with transparent materials, raising concerns about the greenhouse effect and its potential to compromise indoor comfort. In this context, the objective of this study is to develop a methodology and model to assessing and optimizing roof covering designs. The model consists of two phases. The first phase involves conducting a visual harmony analysis within the developed algorithm, using parametric model pattern alternatives created in Rhinoceros3D/Grasshopper3D. The second phase focuses on optimizing visual comfort parameters, including sDA, UDIuseful, UDIupper and DGP. The optimal pattern is determined by evaluating a variety property of transparent surfaces such as solar heat gain, light transmittance, and area using the Ladybug, Honeybee plugins. The options constitute via Colibri plugin. The case study chosen for this investigation is one of Mimar Sinan’s building in Istanbul. This choice is motivated by the increasing intervention of enclosed to open courtyards in madrasah buildings from this era. The construction system is proposed to use steel, with ETFE for the transparent surfaces. Consequently, the outcomes demonstrate the model is feasible for interventions.
Keywords: Building physics; Computer aided design; Contemporary addition; Courtyard covering; Natural lighting; Visual comfort